ПРАВА НЕРОЖДЁННОГО РЕБЁНКА И ПРОФИЛАКТИКА НАРУШЕНИЙ РЕПРОДУКТИВНОГО ПОТЕНЦИАЛА ЖЕНЩИН - Большакова, Полина Николаевна (SUPREMANCE OF LAW, 2017)
The article considers becoming and development of public policy of health care in relation to the unborn child, legislative and normative acts in area of legal defense of motherhood and childhood according international recommendations. The situations making possible to detect reserves of enhancement of effectiveness of profile official documents are analyzed. The aspects concerning future of national medical science.